Evaluation of Knowledge Level on Self-Medication for Headache Among Students at Universitas Muhammadiyah Yogyakarta: A Descriptive Study - Andy Kurniawan Saputra; Pinasti Utami; Deansyah Yanuar Pratama (Universitas Wahid Hasyim Semarang, 2026)
The extent of understanding regarding self-medication for migraines among students remains comparatively limited. Nonetheless, there has been an increasing trend in the availability of data on medications on the internet. The regular use of over-the-counter (OTC) drugs for headache management requires proactive measures to ensure safe and appropriate self-medication practices. This study seeks to determine the level of knowledge regarding self-medication for headaches among students at Universitas Muhammadiyah Yogyakarta. This study employed a descriptive design, using an observational technique and a cross-sectional methodology, with a sample of 369 students from Universitas Muhammadiyah Yogyakarta. A reliable, standardized online questionnaire was used to evaluate the subjects' knowledge. The data will be presented descriptively to illustrate the students' understanding of self-medication for headaches. The survey indicated that 87.8% of students had a